Voluntary wheel running promotes lymphangiogenesis in slow-twitch muscle in young mice - Tamura, Yuma; Kawashima, Takafumi; Kodama, Aoi; Ji, Rui-Cheng; Itoh, Yuta; Agata, Nobuhide; Kawakami, Keisuke (Frontiers in Physiology, 2025)
IntroductionLymphatic vessels contribute to tissue homeostasis. Although the lymphatic vessels in skeletal muscle are known to undergo structural changes under certain conditions, such as atrophy and injury, effects of exercise on intramuscular lymphatic vessels remain unclear.MethodsThis study was aimed at investigating whether 8 weeks of voluntary wheel running (VWR) induces histological changes in lymphatic and blood capillaries, and whether these responses are related to age and myofiber type. Young (3-month-old) and aged (18-month-old) male C57BL/6 mice were assigned to sedentary or VWR groups. The soleus (SOL; slow-twitch) and plantaris (PLAN; fast-twitch) muscles were analyzed using immunohistochemistry and quantitative polymerase chain reaction.ResultsIn young mice, VWR increased the quantity of type I myofibers and significantly enhanced the density of lymphatic vessels and blood capillaries in the SOL, besides upregulating the expression of vascular endothelial growth factors, VEGF-C and VEGF-D. These changes were not observed in aged mice or in the PLAN of mice in either age group.DiscussionAlthough aged mice showed a similar increase in the quantity of type I myofibers, they did not exhibit corresponding vascular remodeling, which suggests that aging reduces responsiveness to exercise-induced angiogenic and lymphangiogenic signals. Overall, these findings indicate that VWR promotes lymphangiogenesis and angiogenesis in slow-twitch muscle in young mice, probably as an adaptive response to meet the increased oxygen demand. Exercise-induced vascular and lymphatic remodeling in skeletal muscle is significantly influenced by age and myofiber type, highlighting a reduced adaptive capacity of aged muscle that may impact strategies for promoting vascular health through physical activity.